Mental Training for Athletes in Achieving Maximum Performance - Widya Putri, Mega; Nuari Panggraita, Gilang; Tresnowati, Idah; Nooryana, Syavira (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Preparing athletes to be ready for competitions needs to be done as early as possible through systematic mental training procedures and processes, which take a considerable amount of time. The goal of training is to achieve performance. To achieve maximum performance, physical, technical, tactical, and mental abilities are required. These four elements are inseparable. Sometimes athletes already have good physical, technical, and tactical conditions, but experience a mental decline during competition. Observing this phenomenon, it is important to implement mental training in facing competitions. Mental training plays a significant role for athletes to prepare strong mental readiness, especially in facing competitions. Mental training involves all aspects of psychology in dealing with various pressures during competitions. There are three mental training techniques that need special attention according to practical needs in athlete training to face competitions. Proper mental training is necessary to enhance good mental quality for athletes. It is hoped that through this mental training, athletes can achieve their best performance. From this activity, it can be concluded that a champion's mentality is a skill possessed by someone, where this skill is not obtained or brought from birth, but is formed due to the influence of the surrounding environment and the athlete's own will. It can be concluded that mental training plays a significant role for athletes to prepare strong mental readiness, especially in facing competitions.